Potential of enzymatically hydrolysed seaweed products as cost-effective nutrient media for growth and lipid enhancement in the marine microalga Nannochloropsis salina: Seaweeds as bio-stimulants for lipid enhancement of microalgae - Krishna Moorthy Abarna; V. Rani; P. Padmavathy; P. Jawahar; A. Uma; C. Kalidas (Indian Journal of Fisheries, 2022)
Enzymatically hydrolysed seaweed products (EHSPs) prepared from the red seaweed, Gracilaria corticata (EHSP-1) and brown seaweed, Stoechospermum marginatum (EHSP-2) contained abundant levels of macro, micro and trace elements necessary to fulfil the nutritional requirement of the microalga Nannochloropsis salina. EHSP-1 had higher levels of N, P, K and Fe in comparison with EHSP-2. The growth performance of N. salina suggests that EHSP-1 was more efficient than EHSP-2. The growth rate of N. salina in EHSP-1 was 1.07 times higher than the control whereas in EHSP-2 the growth rate was 0.58 times lower than the control. The maximum biomass concentration of N. salina was achieved in EHSP-1 and EHSP-2 were 0.37 and 0.21 g l-1 with a biomass productivity of 0.027 and 0.0152 g l-1 d-1 respectively. The results of biochemical analyses also suggest that protein, pigment and lipid yield of N. salina was positively stimulated by EHSP. The findings suggest that the best concentration of EHSP-1 and EHSP-2 to achieve maximum biomass and lipid production of the marine microalga N. salina were 8 and 4% respectively. EHSP-1 enhanced the biomass and lipid production without affecting the nutritional properties of N. salina suggesting its potential applicability in aquaculture, biofuel and other related industrial sectors. Keywords: Cellulase enzyme, Indigenous seaweed resources, Nannochloropsis salina, Nutrient rich media